Insight into hypoglycemia frequency in congenital hyperinsulinism: evaluation of a large UK CGM dataset. Issue 3 (8th June 2022) - Worth, Chris; Tropeano, Yesica; Gokul, Pon Ramya; Cosgrove, Karen E; Salomon-Estebanez, Maria; Senniappan, Senthil; Dastamani, Antonia; Banerjee, Indraneel
Abstract : Introduction: Hypoglycemia is often recurrent and severe in patients with congenital hyperinsulinism (CHI). However, there is little information regarding frequency or patterns of episodes to inform clinical management and future trial design. Research design and methods: We aimed to describe frequency and patterns of hypoglycemia by varying thresholds through a large continuous glucose monitoring (CGM) dataset. Through the UK CHI centers of excellence, data were analyzed from patients with CHI over a 5-year period. Hypoglycemia thresholds of 3.0 (H3.0), 3.5 (H3.5) and 3.9 (H3.9) mmol/L were used to test threshold change on hypoglycemia frequencies. Results: From 63 patients, 3.4 million data points, representing 32 years of monitoring, were analyzed. By UK consensus threshold H3.5, patients experienced a mean 1.3 hypoglycemic episodes per day. Per cent time hypoglycemic increased from 1.2% to 3.3% to 6.9% when threshold changed from H3.0 to H3.5 and H3.9. Merged data showed periodicity of hypoglycemia risk in 24-hour periods in all patients. Conclusions: We have evaluated a large dataset to provide a comprehensive picture of the frequency and patterns of hypoglycemia for patients with CHI in the UK. These data establish a baseline risk of hypoglycemia by CGM and provide a framework for clinical management and clinical trial design.